2016
DOI: 10.2352/issn.2470-1173.2016.19.coimg-169
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Resolution Enhancement of Hyperspectral Images via Sparse Representations

Abstract: High-spectral resolution imaging provides critical insights into important computer vision tasks such as classification, tracking, and remote sensing. Modern Snapshot Spectral Imaging (SSI)systems directly acquire the entire 3D data-cube through the intelligent combination of spectral filters and detector elements. Partially because of the dramatic reduction in acquisition time, SSI systems exhibit limited spectral resolution, for example, by associating each pixel with a single spectral band in Spectrally Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…A disruptive new concept in state-of-the-art signal processing refers to the sparse representations framework, where one seeks a sparsity-promoting decomposition of the input by exploiting available training observations. Particular applications of the sparse representations framework in spectral imaging involve denoising [17] and super-resolution [18], [19] among others. Recently, Degraux et al presented a 3D inpainting method for demosaicing SSI measurements, where reconstruction is achieved by exploiting appropriate sparsifying dictionaries, wavelets for the spatial dimension and DCT for the spectral [20].…”
Section: State-of-the-art Spectral Demosaicingmentioning
confidence: 99%
“…A disruptive new concept in state-of-the-art signal processing refers to the sparse representations framework, where one seeks a sparsity-promoting decomposition of the input by exploiting available training observations. Particular applications of the sparse representations framework in spectral imaging involve denoising [17] and super-resolution [18], [19] among others. Recently, Degraux et al presented a 3D inpainting method for demosaicing SSI measurements, where reconstruction is achieved by exploiting appropriate sparsifying dictionaries, wavelets for the spatial dimension and DCT for the spectral [20].…”
Section: State-of-the-art Spectral Demosaicingmentioning
confidence: 99%
“…Redundancy Reduction: Because the dimension of HSI data is often large (tens of thousands), this causes a high computational cost in object detection applications, especially in deep learning approaches [14]. On the other hand, the sparseness of HSI data has been demonstrated in earlier works [15,16,20]. Therefore, selecting an appropriate subset of bands was considered an efficient process.…”
Section: Challenges and Pre-processing Techniquesmentioning
confidence: 99%
“…For example, among attempts using support vector machine (SVM) [32,2,46], a more recent work [36] was based on independent component analysis and morphological features. Meanwhile, sparsity-based algorithms [15,16,20] showed that the sparse representation of a pixel can predict the class label of the test sample better than classical SVMs. Recently, deeplearning approaches [14,40,17,53,28,35,39,41,51,52,50,43,48] make use of hierarchically extracted deep features.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled dictionary learning relies on generating a pair of dictionaries which jointly encode the active S α , and the passive S p feature spaces, where the signals have sparse representations in terms of the trained dictionaries [16]. The main task is to recover a coupled dictionary pair D α and D p for the spaces S α and S p , respectively [10], and their corresponding sparse codes W α and W p , under the constraint W α = W p , by solving the following sparse matrix decomposition problems: argmin…”
Section: Coupled Dictionary Learningmentioning
confidence: 99%